O uso do blog no ensino de jovens e adultos: uma investigação em linguística aplicada - Fonseca, Lucilene Santos Silva (2009)
Working as a teacher in Education of Young People and Adults in a public school motivated me to create and use a blog to complement the Portuguese lessons. The use of this resource not only aimed at building a bank of materials and activities but also sought to insert students in the digital context. Therefore this research had as objectives to describe and analyze the teacher s experience regarding this resource in Portuguese lessons in groups of young people and adults from the teacher s field notes as well as to identify and evaluate the receptivity of the students in relation to the introduction and use of the blog from the comments in it and questionnaires. The theoretical basis of this research are centered on Social-Historical- Cultural Theory (Vygotsky, 1934/1998), on Systemic Functional Linguistics (Halliday, 1994/2000) and on the notion of Appraisal (Martin, 2003, 2005) as well as on the concept of Critical Reflection (Schön, 2000). This research was developed based on the qualitative research paradigm (Flink, 2004) and it is characterized as a case study (Lüdke, 1986; Ventura, 2007). At the end of this work, its contributions to the area of new technologies applied to education became evident, specifically in the courses for young people and adults, since as a result of the process generated by means of the blog implementation, I show that it is possible for the students view the computer and its multiple resources as an efficient alternative to deepen their knowledge